The LIVES-FORS cohort survey: A longitudinal diversified sample of young adults who have grown up in Switzerland. (1st July 2019) - Spini, Dario; Morselli, Davide; Elcheroth, Guy; Gauthier, Jacques-Antoine; Le Goff, Jean-Marie; Dasoki, Nora; Tillmann, Robin; Rossignon, Florence
Abstract : The LIVES-FORS Cohort Study (LCS) is a longitudinal annual survey following a cohort of young adults born between 1988 and 1997 who grew up in Switzerland (initial N = 1, 691). The LCS was launched in 2013 and complements the Swiss Household Panel (SHP) by over-representing the second generation of immigrants ('secondos'). The principal aim of the study is to observe the transition into adulthood with a focus on the life course and on vulnerability processes, comparing participants whose parents arrived in Switzerland as adults to participants whose parents have grown up in Switzerland. The LCS provides rich data both on the factual (such as education, employment and financial situation) and on the self-judgement (well-being, personality and health, for example) dimensions of respondents' lives. The first wave of the LCS used a life-history calendar to collect information on each respondent's past life trajectory. In this first wave, several life trajectories were investigated (residence, cohabitation, couple's relationship, family, activities and health). This paper provides an overview of the LCS with a specific focus on the first four waves (the last data were released in December 2017).